Voters and the Personal Vote: A Counterfactual Simulation - Canache, Damarys; Mondak, Jeffery J.; Cabrera, Ernesto (Political research quarterly, 2000)
Electoral formulas and campaign practices in some nations encourage voters to consider the personal qualifications of candidates for legislative office, whereas individuating information about candidates is unavailable to voters in other nations. Where electoral rules and elite behavior foster the personal vote, the personal vote flourishes. However, it is unclear why voters respond to personal information about candidates. We test two competing hypotheses: that the personal vote reflects a general human tendency to attend to information regarding individuals' personal qualifications; and that the personal vote is an acquired behavior that emerges after voters are socialized to attend to personal information about candidates. We use counterfactual simulations to test these hypotheses. Specifically, we conduct laboratory experiments in which subjects drawn from Mexico and Venezuela—nations in which electoral rules ensure that the personal vote does not flourish—are provided the opportunity to consider candidates' personal qualifications. Results are consistent with the hypothesis that the personal vote stems from a general tendency in human decision making.